Qatar Foreign Policy in Middle East Conflict Mediation - Kusumawijaya, Kresna; Machmudi, Yon (Journal Of Middle East and Islamic Studies, 2022)
Qatar's role as a regional mediator allowed it to emerge even further into global politics and it’s a step toward creating its own evolving independent political persona. As a mediator, Qatar has left its choices open to develop diplomatic relations with non-state actors and countries that have controversies in the Middle East. This research uses a case study approach to explore information about several foreign policies carried out by Qatar against countries and non-state actors in the Middle East. The results of this study show that Qatar, with its rationality, weighs the benefits for the personal interests of the state. To achieve its goals, Qatar will choose consistent and stable preferences, compare the benefits and costs of all available options, and choose the most optimal choice that is maximizing results. From all the mediations that have been carried out, Qatar mostly has used its country's ability to eliminate conflicts in the region. Therefore, the case study of Qatar then illustrates that a country can directly or indirectly use the capacity of the state to engage with non-state actors who are deemed to have benefits for Qatar itself.